The Japanese way of parenting : and what it taught me about raising (mostly) calm, caring, capable kids - Katayama, Lisa
While Bringing Up Bébé introduced readers to the French way of raising obedient children who are seen but not heard, and Battle Hymn of the Tiger Mother shared an in iron-will parental approach to creating high-achieving kids, Lisa Katayama's Parenting the Japanese Way brings the principles of Japanese parenting to Americans, emphasizing unconditional love, community, and harmony with nature, to nurture children who are well-behaved, respectful, and creative. Japan is well known for its culture of respect, technological innovations, delicious food, peaceful vibes, and deep connection to nature. The source code to all of it is the way the Japanese view childhood--as a time of rigorous training for societal participation, where they learn from the start that are just one part of a larger whole. Katayama takes readers along with her as she travels back and forth from her motherland of Tokyo to the East Bay of California to expose her two American, mixed-race kids to the Japanese way of parenting. Readers will be inspired to take some of her insights--the importance of routine and ritual or the benefits of simplified spaces or the power in making everyday things cute -- and adopt them into their own parenting, no matter where they live.